Robustness Measure of China’s Railway Network Topology Using Relative Entropy - Fenling Feng; Lei Wang (Discrete Dynamics in Nature and Society)
This study focused on China’s railway network topology issue from a robustness measure perspective. Relative entropy is used in the study as a measurement of robustness of railway network topology. It is found that the entropy-based measure provides more informative analyses compared to a traditional graph measure. The results indicate that the railway network in the 12th five-year plan has improved robustness when compare to 2008 with respect to deliberate and random attacks.